Servicio al cliente en El Pet Shop D´Ena Moreira de la ciudad de Babahoyo, periodo 2022. - Paladines Moreira, Katiuska Salome (2023)
The study was carried out in the family business Pet Shop D'Ena Moreira, owned by Jesús Salomón Paladines Tituben. This company offers veterinary care services for small and large species, grooming for dogs and cats, sale of accessories and medicines for pets, considering the high presence of pets in the homes of Babahoyo. The company has been operating since approximately 2008 and has seen changes in its location over the years. The objective of the study focused on analyzing how customer service is provided at Pet Shop D'Ena Moreira. The main findings indicate that customers have an adequate perception regarding the service, the quality of the products and the information provided. However, concerns were identified related to a lack of parking and safety in the area. The methodological approach was descriptive, using structured interviews and questionnaires, aimed at the manager and regular clients. This study is located in the research line: Financial, administrative, tax management, audit and control, specifically the subline: Public and private companies and institutions, and is related to the broader project of management of administrative management processes in the public sector. and private.